2015
DOI: 10.2146/ajhp140274
|View full text |Cite
|
Sign up to set email alerts
|

ASHP national survey on informatics: Assessment of the adoption and use of pharmacy informatics in U.S. hospitals—2013

Abstract: This survey found widespread use of pharmacy informatics and technology across the entire medication-use process. Considerable progress was demonstrated in meeting meaningful-use measures for EHRs and meeting the recommendations of the ASHP PPMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 22 publications
1
37
0
1
Order By: Relevance
“…8, 30-32 A recent survey indicated that only 10.7% of hospitals with e-prescribing systems electronically prescribed Schedule II medications in 2013, so most patients must still bring a paper prescription to the pharmacy. 33 Although opioid misuse is a national problem, legitimate access to opioids can also be challenging, particularly for individuals living in predominantly minority areas 30 and for those with chronic pain for whom prescribing of opioid analgesics is frequently necessary. The rescheduling debate for hydrocodone/acetaminophen lasted for years and even prompted congressional action.…”
mentioning
confidence: 99%
“…8, 30-32 A recent survey indicated that only 10.7% of hospitals with e-prescribing systems electronically prescribed Schedule II medications in 2013, so most patients must still bring a paper prescription to the pharmacy. 33 Although opioid misuse is a national problem, legitimate access to opioids can also be challenging, particularly for individuals living in predominantly minority areas 30 and for those with chronic pain for whom prescribing of opioid analgesics is frequently necessary. The rescheduling debate for hydrocodone/acetaminophen lasted for years and even prompted congressional action.…”
mentioning
confidence: 99%
“…[3,12] The results of Pharmacy technology in drug distribution network included Automated transportation system lower that results in report by Alsultam et al and Pedersen, C et al and Fox, B et al while the finding of centralized units dose (Cart filling machines, robotic arms) better than Alsultan report but lower than Pederson c et al and Fox, B et al, result. [4,7,12] The MOH hospital recently started with the automated distribution system, and there some improvement of utilization new pharmacy technology with one-third of hospital pharmacies had planning project for that but still far away from developing countries.…”
Section: Discussionmentioning
confidence: 74%
“…[9][10] Other investigation emphasized on pharmacy automation and technology or pharmacy informatics. [11][12][13][14] However, the most of the local investigation not included the ministry of health hospitals. It is seldom to find in Kingdom of Saudi Arabia or Gulf and Middle East counties studies about pharmacy informatics system in-depth detail manner.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation rates in European hospitals fall far below those in the United States, where for the last decade accreditation has been linked to implementation 1 2. Multidisciplinary collaboration is essential, with pharmacy input and the creation of a smart pump drug library recognised as often being limiting, yet crucial factors, to implementation 3.…”
mentioning
confidence: 99%